STUDY ON MULTIPOTENT MEDICINAL ASPECTS OF SCHIMA WALLICHII (BARK) FROM NAGALAND, NE INDIA - BHATTACHARJEE, MINAKSHI; SEMA Y, VITOLU; PRATIMSARMA, MANASH (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study focuses on the multipotent medicinal aspects of Schima wallichii bark. Methods: The ethanol and water extracts of the plant were investigated its phytochemical, antibacterial, antioxidant, and anticoagulant as per the standard method. Results: S. wallichii bark extract was effective against Staphylococcus aureus. It was also found to be a good antioxidant having an IC50 value of 98.7 in ethanolic extract. Further, the water extract increased in prothrombin time to 57.7 s against normal (12.3 s). The different phytochemicals, namely tannin, saponins, steroids, terpenoids, flavonoids, and glycosides, were present. Since the findings showed very less percent inhibition in comparison to curcumin-treated cells, thus both the extracts were both not effective in the antiproliferative assay. Conclusion: We conclude that this plant is a good candidate for developing a natural drug.